The Role of Physical Activity in Managing Endometriosis: A Comprehensive Review - Papież, Magdalena; Bartkiewicz, Karolina; Kostro, Julia; Libera, Anna; Jędra, Zofia; Domosud, Karolina; Makulec, Gabriela; Zienkiewicz, Damian; Novik, Lizaveta; Kozicki, Maciej (Quality in Sport, 2026)
Endometriosis is a chronic gynecological disorder affecting millions of women worldwide, leading to chronic pain, infertility, and reduced quality of life. Conventional treatment methods, including hormonal therapy and surgical interventions, often do not provide sufficient relief or have long-term side effects, increasing the need for complementary therapies [1]. Physical activity is emerging as a non-pharmacological strategy that may help alleviate endometriosis symptoms through its impact on inflammatory processes, hormone regulation, and pain modulation [2]. Various studies have investigated the relationship between exercise and endometriosis, suggesting potential benefits such as reduced pain intensity, improved circulation, and better overall well-being. However, discrepancies in study designs, exercise protocols, and patient adherence make it difficult to establish standardized guidelines for physical activity as a therapeutic approach [3,4]. This review synthesizes the current research findings on the relationship between physical activity and endometriosis, explaining the biological mechanisms involved and highlighting the need for further well-controlled studies to develop practical recommendations.